RESPONSIVENESS OF PATIENT COMPLAINTS VIA SOCIAL MEDIA AT BIDADARI HOSPITAL, BINJAI - Maharani Siregar; Dasrun Hidayat; Yani Restiani Widjaya (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
ABSTRACT This study aims to formulate the responsiveness process of handling complaints through social media and how officers interpret responsiveness, as well as how organizational dynamics influence responses to patient complaints submitted through social media at Bidadari Binjai Hospital. The phenomenon raised is that there is a research gap regarding the responsiveness of handling complaints via social media in hospitals which is considered slow. This shows that the speed of response is an important aspect in handling complaints via social media. The methodology used was a descriptive qualitative approach. Primary data was obtained through field observations and in-depth interviews with management and patients. Data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing. Results study show that responsiveness service in handling complaint patient via social media at Bidadari Hospital Binjai has implemented through mechanism reception complaints, verification, coordination with related units, follow up continue, and delivery results settlement to patient. Responsiveness officer shown through polite, empathetic, interactive communication, and​ professional with ensure information provided​ easy understood as well as guard confidentiality patients. However, research Also find a number of constraints, namely Not yet availability of special SOPs handling complaint through social media, limitations source Power humans, and double task affected officers​ on slowness time response to part complaint. In overall, handling complaint through social media has walk with good,but Still need strengthening system And source Power For increase quality responsiveness service.